2022
DOI: 10.3390/drones6030062
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Approach to Time Savings and Cost Competitiveness Assessments for Drone Transport of Biologic Samples with Unmanned Aerial Systems (Drones)

Abstract: Unmanned aerial vehicles (UAVs, drones) are expected to save transport time and improve service reliability for transport of biologic samples, but few studies have evaluated the potential time savings of such services. The total transport time defined as time from sample ready for transport until arrival at the laboratory was used to assess the absolute and relative time savings of drones compared with ground transport, using ground distances from 4–7 km (urban model) to 179–262 km (rural district routes) with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Some minutes saved may have marginal clinical significance in specific healthcare systems where patients may wait for months for their first contact with healthcare provisions. 14 Furthermore, to what extent faster transport will influence the efficiency of healthcare to any significant degree may be an open research question.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some minutes saved may have marginal clinical significance in specific healthcare systems where patients may wait for months for their first contact with healthcare provisions. 14 Furthermore, to what extent faster transport will influence the efficiency of healthcare to any significant degree may be an open research question.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, such multiple routings would not be relevant for future drone services because such serial transports would include legs with multiple drone takeoffs and landings, consuming significant energy for hovering and transport times. 14 We, therefore, intended to consider direct routings, ie, round trip tours between two locations. We measured all time intervals during the shadowing of the tours and also interviewed the drivers about the delays as they occurred.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many researchers have proven the feasibility of using drones as a reliable component, so the use of drones has spread in many sectors. For example, the authors in [18] presented drones as a potential transporter for biologic samples; their research concluded that while drones achieved modest gains for short-distance transportation, long-distance transport models with proper scheduling and suciently high drone speeds oer more promising time reductions. Additionally, the authors in [5] used drones equipped with smart capsules to introduce a veried method of transporting blood products, a method that is designed especially for an urban environment.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Budget: Consider financial constraints and design the UAV system within the allocated budget [103]. Cost-Benefit Analysis: Evaluate the cost-effectiveness of different design choices [104].…”
Section: Cost and Budget Constraintsmentioning
confidence: 99%